2016
DOI: 10.2522/ptj.20150501
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Global Postural Re-education in Patients With Chronic Nonspecific Neck Pain: Randomized Controlled Trial

Abstract: The results suggest that GPR was more effective than MT for reducing pain after treatment and for reducing disability at 6-month follow-up in patients with chronic nonspecific NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 42 publications
(37 reference statements)
2
38
0
6
Order By: Relevance
“…The other three studies excluded individuals who suffered from NP with a "non-mechanical cause" [45], reported "any medical sign suggestive of a non-musculoskeletal aetiology" for their NP [43], or were diagnosed with a "specific cause for the neck pain"; e.g., organic disorders or systemic diseases [48]. A "clear aetiology" [57] or a "specific cause" [57,58] for the NP was also listed as an exclusion criterion in three other trials. Yet, none of the latter studies mentioned visceral or organic disorders as possible specific causes for the NP.…”
Section: Eligibility Criteria (Inclusion and Exclusion Criteria) Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three studies excluded individuals who suffered from NP with a "non-mechanical cause" [45], reported "any medical sign suggestive of a non-musculoskeletal aetiology" for their NP [43], or were diagnosed with a "specific cause for the neck pain"; e.g., organic disorders or systemic diseases [48]. A "clear aetiology" [57] or a "specific cause" [57,58] for the NP was also listed as an exclusion criterion in three other trials. Yet, none of the latter studies mentioned visceral or organic disorders as possible specific causes for the NP.…”
Section: Eligibility Criteria (Inclusion and Exclusion Criteria) Usedmentioning
confidence: 99%
“…Yet, none of the latter studies mentioned visceral or organic disorders as possible specific causes for the NP. Some other visceral sources of NP were enumerated in other clinical trials: (a) hepatitis [37]; (b) systemic disorders, including metabolic disease [30,35,36,41,46,57,58]; (c) abuse of alcohol and drugs [37,54]; (d) rheumatic disease [31][32][33]35,37,46,49,[51][52][53]55,56,58]; (e) cancer [30,31,35,37,42,[51][52][53][55][56][57]; (f) HIV [37]; and (g) infection [30,33,34,40,45,47,57]. Pregnancy was also included as exclusion criteria in almost half of the trials [30,32,34,37,38,…”
Section: Eligibility Criteria (Inclusion and Exclusion Criteria) Usedmentioning
confidence: 99%
“…Exercises, such as gymnastics and dynamic stretching 21) , and strategies for improving working methods, such as optimizing worker posture 22) , are reportedly effective for improving chronic musculoskeletal pain. Pain-based functional disorders have also been improved by a combination of cognitive behavioral therapeutic approaches and exercise 23) .…”
Section: Relationship Between the Site Of Chronic Musculoskeletal Paimentioning
confidence: 99%
“…The design strategy is based on three key factors, f = number of factors which is usually taken as 1 followed by L = number of possible levels and N = replications numbers. Starting design phase is to set the hypothesis using ANOVA making the objective to test the right hypotheses around the means of treatment and to approximate them [12]. If is the jth response observation for specific factor treatment level ; observations, .…”
Section: Completely Randomized Designmentioning
confidence: 99%